Quantum chemical pKa prediction for complex organic molecules. Issue 12 (6th December 2017) - Philipp, Dean M.; Watson, Mark A.; Yu, Haoyu S.; Steinbrecher, Thomas B.; Bochevarov, Art D.
Abstract: Numerous types of quantum chemical calculations and protocols have been successfully applied to computing p K a of small, uncomplicated organic molecules. Here, we argue for the need to shift attention to more challenging molecules that are marked by an interplay of complicating factors such as conformational, tautomeric, steric, and other effects. The challenge is not in choosing the right quantum chemical method and solvation model but in combining the existing methods to simultaneously and accurately describe the breadth of chemical and physical phenomena that give rise to the experimentally observed p K a . The complexity of the phenomena that must be considered begs for the need for a greater automation of p K a prediction workflows. We review our experience with these challenges and outline paths for future progress in the direction of tackling p K a prediction of complex organic molecules. Abstract : p K a prediction of complex molecules characterized by large size, multiple functional groups, tautomerism, symmetry, and other complicating factors calls for sophisticated quantum chemical workflows that explicitly take into account 3D effects and conformational flexibility. This perspectives discusses challenges and possible steps forward in this difficult research field.